Energy-oriented cruising strategy design of vehicle platoon considering communication delay and disturbance. (October 2019) - Xu, Liwei; Zhuang, Weichao; Yin, Guodong; Bian, Chentong
Highlights: A new time-domain-based energy-oriented spacing policy is proposed. Discrete-time vehicle platoon system integrating communication delay and disturbance is provided. Less conservative discrete robust platoon control methodology is developed. L 2 -based string stability and its criterion of the discrete platoon are given. Abstract: This paper presents a discrete control framework for a homogeneous vehicle platoon, which can minimize the energy consumption of each vehicle while ensuring the platoon string stability under external interference and communication delay. First, a novel variable spacing strategy named as the energy-oriented spacing policy is proposed by comparing the geometry relationship of each vehicle which drives at energy-optimal speed and the ideal speed under the constant spacing policy. Then, based on the energy-oriented spacing policy, the dynamics of a homogeneous discrete vehicle platoon composed of several pure electric vehicles are built, including the communication delay and external disturbance. Second, a discrete robust platoon controller that can reduce the conservatism of the control system is designed based on the Lyapunov-Krasovskii theorem and H ∞ method, which drives each vehicle at their energy-optimal speed while ensuring the string stability of platoon under communication delays and interferences. Third, the L 2 -based string stability of the discrete platoon is defined, and its string-stable criterion is given under communication delays and external disturbances. Simulation results indicate that the proposed energy-oriented spacing policy and the discrete controller can enable efficient driving of each vehicle while ensuring the platoon string stability. The energy consumption of the whole platoon is, respectively, reduced by 7.3% and 5.7% compared to the vehicle platoon controllers with constant spacing policy and constant time headway policy.